Mechanism of salvianolic phenolic acids and hawthorn triterpenic acids combination in intervening atherosclerosis: network pharmacology, molecular docking, and experimental validation - Zhai, Qu; Shang, Shixi; Zhang, Zihan; Sun, Lihua; Huang, Ying; Feng, Shuyi; Wu, Qian; Cui, Haifeng; Shi, Xiaolu (Frontiers in Pharmacology, 2025)
BackgroundThis study employs network pharmacology and molecular docking methods in conjunction with animal experimentation to elucidate the underlying mechanism by which the combination of salvianolic phenolic acids and hawthorn triterpenic acids (SHC) exerts its therapeutic effect on carotid atherosclerosis (AS) in ApoE−/− mice.MethodsA network pharmacology research approach was used to predict potential core targets for SHC intervention in atherosclerosis. The predictions were subsequently validated through the implementation of animal in vivo experiments. ApoE−/− mice were randomly assigned to three experimental groups, namely, a model group, an atorvastatin group, and an SHC group. After the administration period, the plaque area in the carotid artery and aortic arch, blood lipid levels, malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), and nitric oxide (NO) content were measured. Additionally, the expression of PI3K, Akt, NF-κB, JNK1, ERK1/2, and p38-MAPK in the aortic arteries was analyzed. Based on the protein expression results, molecular docking was used to predict the binding activity between the core compounds and core targets.ResultsA total of 23 core compounds were identified in SHC, and 55 core targets of SHC were screened as potential targets for intervention in AS. The results of the enrichment analysis indicated that the principal mechanisms through which SHC exerts its effects in AS are associated with lipid metabolism and the PI3K-Akt and MAPK pathways. The results from animal experiments demonstrated that atorvastatin and SHC markedly reduced the area of carotid plaque and downregulated the levels of TC and LDL-C in ApoE−/− mice. The administration of SHC was associated with an increase in SOD activity and a reduction in NO levels in the livers of mice. Furthermore, SHC was observed to downregulate the expression of NF-κB and p38-MAPK in the carotid region. The results of molecular docking demonstrated that the core compounds of SHC, including salvianolic acid A, B, and C, maslinic acid, ursolic acid, and oleic acid, were capable of stably binding to the core targets NF-κB and MAPK14.ConclusionIt is hypothesized that SHC may reduce lipid deposition and plaque formation in AS by regulating blood lipids, a process that may be closely linked to the inhibition of inflammatory regulator expression, including NF-κB and p38-MAPK.